2016
DOI: 10.1371/journal.pone.0152331
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-Dependent Misperception of Subjective Visual Vertical during and after Transcranial Direct Current Stimulation (tDCS)

Abstract: Pathologic tilt of subjective visual vertical (SVV) frequently has adverse functional consequences for patients with stroke and vestibular disorders. Repetitive transcranial magnetic stimulation (rTMS) of the supramarginal gyrus can produce a transitory tilt on SVV in healthy subjects. However, the effect of transcranial direct current stimulation (tDCS) on SVV has never been systematically studied. We investigated whether bilateral tDCS over the temporal-parietal region could result in both online and offline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
2
10
0
11
Order By: Relevance
“…Restoration of "normal" bilateral PIVC balance may provide an opportunity for training more accurate postural control at least for a brief initial interval of tDCS. These findings also indicate that vestibular stimulation via GVS did not change mean COP-Xs as explained in previous studies with healthy subjects [6,7]. The lack of change via GVS may strengthen the argument that postural awareness and control are cortical functions that prioritize visual and proprioceptive sensory input over direct vestibular sensory input.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Restoration of "normal" bilateral PIVC balance may provide an opportunity for training more accurate postural control at least for a brief initial interval of tDCS. These findings also indicate that vestibular stimulation via GVS did not change mean COP-Xs as explained in previous studies with healthy subjects [6,7]. The lack of change via GVS may strengthen the argument that postural awareness and control are cortical functions that prioritize visual and proprioceptive sensory input over direct vestibular sensory input.…”
supporting
confidence: 83%
“…The lack of change via GVS may strengthen the argument that postural awareness and control are cortical functions that prioritize visual and proprioceptive sensory input over direct vestibular sensory input. The current density used in our study (2 mA/25 cm 2 or 0.08 mA/cm 2 ), as described previously [6], may have been too weak to produce an adequate, prolonged neuronal response.…”
mentioning
confidence: 87%
“…This functional distinction between TPJ and early visual cortex is in line with the role of TPJ in multisensory integration for perception of upright. A significant SVV shift has also been shown using transcranial direct current stimulation (tDCS) over TPJ ( 258 ). This shift was dependent on tDCS electrode placement, with SVV deviation toward the side of anode placement.…”
Section: Perception Of Upright and Cerebral Cortexmentioning
confidence: 99%
“…After stroke, vertical misperception and postural imbalance are frequent and negatively impact functional recovery ( 14 – 17 ). Targeting the TPJ, we recently showed that it is possible to manipulate perception of verticality ( 18 ) and postural control ( 19 ) in a polarity dependent manner during and after conventional tDCS over TPJ bilaterally (bipolar-balanced montage) ( 20 ). These studies provided support for restoration of visual vertical misperception and improved postural imbalance after stroke using tDCS over TPJ ( 19 ).…”
Section: Introductionmentioning
confidence: 99%